Politeness Strategies of Disagreement by English Native Speaker Students - Nadia Yofa Laela Khoirunnisa; Tofan Dwi Hardjanto (Universitas Gadjah Mada, 2018)
This research paper investigates the speech act of disagreement performed by English native speaker students. Particularly, it attempts to examine the politeness strategies used by English native speaker students in realizing disagreement. The data were obtained using Discourse Completion Task consisting of six situations that were completed by twenty students. The results showed that a total of 113 utterances of disagreement were found. The most frequently used strategy was negative politeness (41.6%) since this strategy becomes the most suitable strategy to minimize the imposition of disagreement utterances. The rank is then followed by positive politeness (29.2%), bald on-record (25.7%), and off-record (3.5%).